Upregulation of SPP1 Is a Marker for Poor Lung Cancer Prognosis and Contributes to Cancer Progression and Cisplatin Resistance - Tang, Huaping; Chen, Jianyou; Han, Xiaolei; Feng, Yan; Wang, Fang (Frontiers in Cell and Developmental Biology, 2021)
The chemoresistance of lung cancer is a significant contributor to its high mortality and morbidity rate. There is an urgent need to identify differentially expressed genes in lung cancer patients with a poor prognosis to develop effective means to overcome drug resistance in subsequent treatment. In this study, we identified the secreted phosphoprotein 1 (SPP1) as a potential gene associated with a poor diagnosis of lung cancer patients using the Cancer Genome Atlas analysis, which suggested that the expression of SPP1 in tumor tissues was significantly higher than normal tissues. The high expression of SPP1 was also correlated with tumor grade and poor clinical prognosis. To understand the roles of SPP1 and the DNA methyltransferase 1 (DNMT1), which regulated SPP1 expression, in affecting cell viability, migration and invasion, SPP1 and DNMT1 were overexpressed in the human lung cancer A549 and NCI-446 cells, followed by analyzing cell viability, migration and invasion. We showed that SPP1 promoted the proliferation, migration and invasion of lung cancer cells, and increased the resistance of lung cancer to the chemotherapeutic drug cisplatin. Knocking down SPP1 in cells restored sensitivity to cisplatin. Further, A549 cells without SPP1 overexpression demonstrated lower tumor growth rate than SPP1 overexpression cells using the xenograft tumor mouse model. High expression of SPP1 in lung cancer tumor tissue was caused by the reduced methylation level of its promoter region mediated by DNMT1. Our data suggested that SPP1 can be used as a marker for highly malignant lung cancer and targeting SPP1 may be a potential lung cancer treatment strategy.